INCIDENCE OF HEPATOCELLULAR CARCINOMA IN PATIENTS WITH CHRONIC HEPATITIS C GENOTYPE III AND ADVANCED HEPATIC FIBROSIS AFTER TREATMENT WITH DIRECT-ACTING ANTIVIRALS - KANJU , S; SHERWANI , UK; RAZA , A; SARWAR , S; WADHAK , MA (Biological and Clinical Sciences Research Journal, 2024)
A prospective study was conducted at the Gastroenterology Department of Nishtar Hospital from August 2020 to August 2022 to evaluate the incidence of hepatocellular carcinoma (HCC) in chronic hepatitis C (CHC) patients with hepatic fibrosis or cirrhosis, genotype III, who achieved sustained viral response (SVR) after treatment with direct-acting antivirals (DAAs). The study included a total of 500 genotype III patients diagnosed with F3 and F4, who received a 3-month or 6-month course of DAA regimens. HCC was diagnosed by performing triphasic MSCT, and staging was done. During the follow-up, 50 out of 500 patients were diagnosed with HCC. The patients diagnosed with HCC were primarily elderly males and had higher levels of AST, AFP, and bilirubin, as well as reduced platelets and albumin levels compared to non-HCC patients. In cirrhotic patients, the incidence of HCC per year was 2.920 per 100 people. Advanced age, male gender, increased AFP, and decreased albumin were among the predictors of HCC incidence in F4 patients. The study findings suggest that CHC patients with fibrosis and cirrhosis who achieve SVR after treatment with DAAs have a reduced incidence of HCC.